Correlation between lipidic content and arterial-wall plaque burden: A Lipid Rich Plaque study sub-analysis. (1st November 2022) - Torguson, Rebecca; Mintz, Gary S.; Case, Brian C.; Di Mario, Carlo; Zhang, Cheng; Shea, Corey; Garcia-Garcia, Hector M.; Waksman, Ron
Abstract: Background: Large plaque burden (PB) has been linked to adverse coronary events. We sought to assess the correlation between lipidic content and arterial PB within the Lipid Rich Plaque (LRP) study. Methods: This analysis included 1269 patients and 5743 coronary segments with both evaluable Lipid Core Burden Index (maxLCBI4mm ) and PB. Non-culprit major adverse cardiac events (NC-MACE; defined as a composite of cardiac death, cardiac arrest, non-fatal myocardial infarction, acute coronary syndrome, revascularization, and hospital readmission for angina with progressive stenosis) were assessed by hazard ratios (HR) at 2 years. Results: NC-MACE for segment cohorts in the most vulnerable quadrant of maxLCBI4mm  > 400 and PB >40% was the highest (HR, 3.78 [95% confidence interval (CI) 2.39–5.66]) with similar rates for just PB >40% (HR 1.31 [95% CI 0.81–2.02]) and just maxLCBI4mm  > 400 (HR 1.11 [95% CI 0.10–5.38]). Fewer events occurred in the maxLCBI4mm  ≤ 400 and PB ≤40% quadrant (HR 0.25 [95% CI 0.11–0.50]). Conclusions: Coronary segments with high lipid content but no measurable PB were still associated with events at 2 years. NC-MACE vulnerability increased as the lipidic content and PB increased, with the highest incidence within segments having maxLCBI4mm  > 400 and plaque >40%. Clinical trial registration: The Lipid-Rich Plaque Study (LRP), NCT02033694, https://clinicaltrials.gov/ct2/show/NCT02033694 . Highlights: Large plaque burden (PB) has been linked to adverse coronary events. We assessed correlation between lipidic content and arterial PB in the LRP study. High lipid content but no measurable PB was still associated with MACE at 2 years. Non-culprit MACE vulnerability increased as the lipidic content and PB increased.